Laparoscopic versus open surgery for colorectal cancer in the older person: A systematic review. Issue 3 (September 2015) - Moug, S.J.; McCarthy, K.; Coode-Bate, J.; Stechman, M.J.; Hewitt, J.
Abstract: Background: Laparoscopic surgery is being increasingly offered to the older person. Objective: To systematically review the literature regarding laparoscopic colorectal cancer surgery in older people and compare to younger adult populations. Study selection: We included randomized controlled trials that compared open to laparoscopic colorectal cancer surgery. Older people were defined as being 65 years and above. Outcome measures: Overall survival and post-operative morbidity and mortality. Secondary endpoints were length of hospital stay, wound recurrence, disease-free survival and conversion rate. Results: Seven trials included older people, average age of approximately 70 years. Two reported data specific to older patients (over 70 years): The ALCCaS study reported reduced length of stay and short-term complication rates in the laparoscopic group when compared to open surgery (8 versus 10 days, and 36.7% versus 50.6% respectively) and the CLASICC study reported equivalent 5 year survival between arms and a reduction of 2 days length of stay following laparoscopic surgery in older people. In trials which considered data on older and younger participants all five trials reported comparable overall survival and showed comparable or reduced complication rates; two demonstrated significantly shorter length of stay following laparoscopic surgery compared to open surgery. Conclusion: Large numbers of older people have been included in well-conducted, multi-centre, randomized controlled trials for laparoscopic and open colorectal cancer surgery. This systematic review suggests that age itself should not be a factor when considering the best surgical option for older patients. Highlights: Seven well conducted randomised controlled trials of open versus laparoscopic colorectal cancer surgery have included older people. Age alone should not be a barrier to laparoscopic colorectal cancer surgery. The effect of comorbidity in older people undergoing laparoscopic surgery is less clear and warrants further study.